(untitled) (KASBIT Business Journal, 2026)
Intellectual capital and working capital management are gaining significant importance in achieving sustainable corporate growth, particularly in knowledge-based industries. This study empirically examines the effect of intellectual capital and working capital management on the sustainable growth of Pakistan’s fertilizer industry. The study uses secondary data from 2019 to 2024 for the fertilizer firms of Pakistan. The dependent variable represents the sustainable growth rate, which is used to measure corporate financial sustainability, while the independent variables are intellectual capital efficiency and working capital management efficiency. Control variables include firm size, leverage, and age. Using panel least squares regression analysis, the study finds that intellectual capital has a strong, positive impact on business sustainable growth, which aligns with the Resource-Based View (RBV) theory. Working Capital Management Efficiency reveals a significant but negative association with sustainable growth. This proposes that inefficient working capital management may create liquidity obstacles and slow down long-term performance in the fertilizer industry. The findings highlight that efficient intellectual resource management is a key driver for long-term growth, while working capital practices require further improvement. Particularly in high energy-consuming industries like fertilizer production, this research offers managers and policymakers valuable insights on enhancing internal resource management to achieve sustained corporate growth.